Preliminary Evaluation of Iron Oxide Nanoparticles Radiolabeled with 68Ga and 177Lu as Potential Theranostic Agents - Evangelia-Alexandra Salvanou; Argiris Kolokithas-Ntoukas; Christos Liolios; Stavros Xanthopoulos; Maria Paravatou-Petsotas; Charalampos Tsoukalas; Konstantinos Avgoustakis; Penelope Bouziotis (Nanomaterials, 2022)
Theranostic radioisotope pairs such as Gallium-68 (68Ga) for Positron Emission Tomography (PET) and Lutetium-177 (177Lu) for radioisotopic therapy, in conjunction with nanoparticles (NPs), are an emerging field in the treatment of cancer. The present work aims to demonstrate the ability of condensed colloidal nanocrystal clusters (co-CNCs) comprised of iron oxide nanoparticles, coated with alginic acid (MA) and stabilized by a layer of polyethylene glycol (MAPEG) to be directly radiolabeled with 68Ga and its therapeutic analog 177Lu. 68Ga/177Lu- MA and MAPEG were investigated for their in vitro stability. The biocompatibility of the non-radiolabeled nanoparticles, as well as the cytotoxicity of MA, MAPEG, and [177Lu]Lu-MAPEG were assessed on 4T1 cells. Finally, the ex vivo biodistribution of the 68Ga-labeled NPs as well as [177Lu]Lu-MAPEG was investigated in normal mice. Radiolabeling with both radioisotopes took place via a simple and direct labelling method without further purification. Hemocompatibility was verified for both NPs, while MTT studies demonstrated the non-cytotoxic profile of the nanocarriers and the dose-dependent toxicity for [177Lu]Lu-MAPEG. The radiolabeled nanoparticles mainly accumulated in RES organs. Based on our preliminary results, we conclude that MAPEG could be further investigated as a theranostic agent for PET diagnosis and therapy of cancer.